HDL Receptor SR-B1 Deficiency Increased Inflammatory Dyslipidemia and Adipocyte Hypertrophy and Attenuated the Hepatic Steatosis in Murine Diet-Induced Obesity. (29th May 2020) - Rivera, Katherine; Quiñones, Veronica; Xavier, Aline; Amigo, Ludwig; Fernández-Galilea, Marta; Carrasco, Gonzalo; Cabrera, Daniel; Arrese, Marco; Busso, Dolores; Andia, Marcelo; Rigotti, Attilio
Abstract: Objectives: We tested whether the scavenger receptor, class B type 1 (SR-B1), a physiologically relevant HDL receptor, modulates the metabolic and inflammatory phenotype of obese mice, accompanied by changes in adipocyte and hepatocyte lipid deposits. Methods: Male SR-B1 knock-out (KO) mice and wild-type (WT) littermates were fed for 12 weeks with a high-fat diet (HFD, n = 12 per group) to induce obesity. Animals were euthanized after overnight food deprivation. Blood was obtained and adipose tissue and liver were removed. Plasma or frozen tissues were used for biochemical analyses or assessed by light microscopy and immunohistochemistry. Comparisons between WT and KO mice fed with HFD were performed and differences were considered statistically significant when P < 0.05. Results: Compared to obese WT, obese HFD-fed SR-B1 KO mice showed increased plasma total cholesterol (p < 0.0001) and triglycerides (TG) (p < 0.01) as well as tumor necrosis factor-α (TNF-α) (p < 0.0001) levels. Also, these animals exhibited white fat with larger adipocytes (p < 0.0001) and increased macrophage-based crown-like structure formation (p < 0.01), compared to HFD-fed WT mice, revealing a more inflammatory adipose tissue. These changes in adipose tissue were associated with reduced hepatic steatosis: reduced hepatocyte lipid droplet area (p < 0.0001) and decreased liver TG content (p < 0.0001). In addition, obese SR-B1-deficient mice showed reduced hepatic peroxisome proliferator‐activated receptor-γ (PPAR-γ) expression, more efficient hepatic fatty acid β-oxidation and increased very-low-density lipoprotein (VLDL)-TG secretion compared to obese HFD-fed WT mice Furthermore, liver fatty acid (FA) composition in obese SR-B1-deficient mice revealed a reduction in monounsaturated (MUFA) (p < 0.01), but an increase in polyunsaturated (PUFA) (p < 0.05), fatty acid content, compared to obese WT mice. Conclusions: Our findings demonstrate that SR-B1 expression modulates high fat feeding-associated inflammatory dyslipidemia, adipocyte hypertrophy, and hepatic steatosis; key processes underlying the pathogenesis of highly prevalent chronic diseases, such as obesity and non-alcoholic fatty liver disease (NAFLD). Funding Sources: FONDECYT 1, 150, 399, FONDECYT 1, 180, 525.